NiFeRu Layered Double Hydroxide and Its Derivatives Supported on Graphite Foam as Binder-Free Cathode for Nonaqueous Li-O2 Batteries - Song, Ming; Tan, Hua; Tian, Lin; Li, Jing; Xu, Yan; Shi, Liluo; Sun, Limei; Zhuang, Wenchang; Du, Xihua (Frontiers in Energy Research, 2020)
Li-O2 batteries (LOBs) generally referred as Li-air batteries (LABs) potentially have a high specific capacity among all types of metal-ion batteries but suffer severely from sluggish discharge/charge kinetics. In this work, an integrated binder-free cathode is fabricated that contains NiFeRu layered-double-hydroxide (NiFeRu LDH) nanosheets grown on a 3D conductive graphite foam (NiFeRu LDH@GF). This integrated 3D cathode exhibits a specific capacity of 3085 mAh g-1 and a cycle life of 46. The electrochemical performances of NiFeRu LDH derived metal oxides (DMO@GF) by calcining NiFeRu LDH@GF at 350℃, 450℃ and 550℃ are also been investigated. The 450℃ obtained DMO@GF (450-DMO@GF) exhibits the highest catalytic activity for both oxygen reduction reaction and oxygen evolution reaction. The unique floccule-like and cross-connected structure of the 450-DMO@GF and its low charge transfer resistance are responsible for the outstanding electrochemical performance.